Современные подходы к созданию гепатотропных магнитно-резонансных контрастных препаратов - Нам И. Ф. Ирина Феликсовна; Жук В. В. Владислав Витальевич; Михайлова К. К. Ксения Константиновна; Захаров М. Г. Михаил Григорьевич; Чернов В. И. Владимир Иванович; Фролова И. Г. Ирина Георгиевна; Григорьев Е. Г. Евгений Геннадьевич; Синилкин И. Г. Иван Геннадьевич; Зельчан Р. В. Роман Владимирович; Стасюк Е. С. Елена Сергеевна (2015, 2015)
Заглавие с экрана